HUBUNGAN MOTIVASI BERPRESTASI TERHADAP HASIL LATIHAN FUTSAL EKTRAKURIKULER FUTSAL SMK MIGAS PEKANBARU - Rudi Denri Tua; Aref Vai; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the extracurricular activities at SMK Migas Pekanbaru that do not get enough attention from the school. It can be seen that every futsal match attended by students never produces results, this problem makes students feel a little inferior to participate in extracurricular futsal to determine the relationship between achievement motivation and the results of extracurricular futsal training. The population in this research consisted of students participating in indoor soccer extracurricular activities using a total sampling technique, a total of 17 students. This type of research correlation product moment, the instrument in this research uses a questionnaire completed by students. Based on the results of the study described in the previous chapter and discussed in the discussion, the conclusion of this research is "there is a relationship between performance motivation and the results of extracurricular futsal training at SMK Migas Pekanbaru", namely Fcount = 12,999 > Ftable = 1.246 at α = 5% with dk (n-1 = 1:23) meaning the test is significant such that (Ha).Key Words: Achivement Motivation, Futsal